SYSTEMATIC LITERATURE REVIEW OF INDUSTRY 4.0 IMPLEMENTATION OF PRODUCTIVITY - Yuniar Suprihatin; Yanneri Elfa Kiswara Rahmantya (Jurnal Ekonomi, 2023)
Industrial Technology 4.0 is designed to provide many conveniences from a transactional persepective, to be able to increase work productivity. This disruptive digital-based technology is crushing old methods and replacing them with new ones. However, the presence of this era of disruption is both an opportunity and a challenge for people's lives. This research aims to provide information about the role of using Industry 4.0. in increasing productivity, as a transformation effort towards improvement and creating opportunities to support business development. This study uses the Systematic Literature Review (SLR) method for journal papers published from 2016-2021. Data collection techniques with the methode of observation, interviews, and documentation. This study's results conclude that the industrial sector's most widely implemented Industri 4.0 innovation y is Artificial Intelligence (AI). This innovation is able to increase productivity, especially in the factors of improving production processes and improving customer service.